The challenges and potential options to meet the peak electricity demand in Mauritius - Elahee, Khalil (Journal of Energy in Southern Africa, 2011)
This paper reviews the current challenges facing Mauritius in terms of meeting peak electricity demand. As a fast-developing island-economy with a very high population density, this is a crucial issue. The more so that it imports 80% of its energy requirements in terms of fossil fuels, relies significantly on tourism and needs to protect its fragile ecosystems. The nature of the peak electricity demand and its evolution is firstly analysed. Reference is made to past scenarios for electricity supply, the obstacles to their implementation and their relevance in terms of sustainability. The forecasts underpinning the latter scenarios are found to be over-estimated. Demand-Side Management projects are discussed and their potential to promote an alternative scenario based on revised forecasts are discussed. Hence a new Maurice Ile Durable (Mauritius Sustainable Island, MID) scenario is proposed in view of stabilising the peak demand, reducing the rate of increase of total electricity demand and making the capacity margin positive. The newly-devised scenario is not only more sustainable but also addresses several political and socio-economic issues to bring holistic win-win solutions. Institutional and regulatory reforms as well as a relevant Business Framework are also important in order to meet the challenges of MID. The new scenario relies only on existing technology with an excellent track-record and provides the transition to a more sustainable future.